Extra canal in permanent maxillary first molar in patients undergoing root canal treatment at a tertiary care dental hospital, Nepal - Gharti, Archana; Joshi, Neera; Prajapati, Kranti; Wagle, Sharada Devi; Shrestha, Suraj (Journal of Kathmandu Medical College, 2021)
Background: Permanent maxillary first molar normally has three root canals but it can have extra root canals for which several studies were done in many parts of the globe. However, this type of study to explore extra canal is lagging in the context of Nepal. Objectives: The objective was to determine the percentage of extra canal in permanent maxillary first molar in patients undergoing root canal treatment and to compare the same between male and female. Methods: The descriptive cross-sectional study was conducted in the department of conservative dentistry and endodontics of People’s Dental College and Hospital from 20th December 2019 to 20th December 2020 after receiving ethical approval from Nepal Health Research Council on 18th December 2019 (ERB protocol No 888/2019) . One hundred and eighty permanent maxillary first molar teeth without root canal calcification were enrolled. Convenient sampling was done. Access opening was done and all canal orifices were located and recorded. Data were analyzed using Statistical Package for the Social Sciences (SPSS) version 22.0 with frequency table. Chi-square test was used for inferential statistics. Results: Out of 180 teeth, extra canals were present in 44(24.4%) having more numbers in male than in females. Extra canal was present in the mesiobuccal root. Conclusion: Extra canal in the permanent maxillary first molar is present in Nepalese population with greater number in male than in female. Thus, exploration of the pulp chamber in search of an extra canal is necessary to prevent failure of root canal treatment.